Peace Culture in School: Analyzing the Wahid Foundation's Peace School Program - Nurhadi, Irfan; Amali, Mushlihin; Aulia, Rihlah Nur (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
This article aims to describe the practice of building a peace culture in schools that are packaged through the Wahid Foundation peace school program. This study used a descriptive qualitative method, in which data were obtained through interviews, observation, and documentation. The researcher interviewed the facilitator of the peace school program at DKI Jakarta. Observation and documentation were carried out during the implementation of peace school program activities in narrating building peace culture in School. According to this research, the Wahid Foundation's narrative of the culture of peace was based on the widespread acts of intolerance, bullying, and radicalism that started to appear in educational institutions. This program was established to help with the management of student organizations, the development of school regulations, and the practice of tolerance and peace. Routine study plans, calming social media posts, and insightful online chats were all used to assist. The eventual aim of the Wahid Foundation's peace school program is to nurture students' character by teaching them to respect, value, and be sensitive to others, as well as to make them ambassadors of peace both within and outside of the classroom.